Stratigraphical distribution of the Ordovician conodont Erraticodon Dzik in Argentina - Heredia, Susana Emma (2013)
Three different species of the Ordovician genus Erraticodon Dzik are described and illustrated. E. patu Cooper is reported from the Lower-Midde Ordovician strata of the Acoite and Alto del Cóndor formations. E. cf. E. balticus and E. hexianensis from Middle Ordovician carbonate deposits of the San Juan Formation are analyzed and compared to specimens of these species from Australia, China, Newfoundland, and Baltica. E. patu and E. hexianensis are recorded for first time in the San Juan Formation of Precordillera. The elements of E. cf. E. balticus resemble closely E. balticus Dzik but lack the important denticle on the posterior process of the S elements. An evaluation of the stratigraphic occurrences of these species relative to those of key Lower and Middle Ordovician conodont species such as Trapezognathus diprion Lindström, O. intermedius Serpagli, Baltoniodus triangularis (Lindström), B. navis Lindström, Yangtzeplacognathus crassus (Chen and Zhang) and Eoplacognathus pseudoplanus (Viira) indicates they value for biostratigraphic correlation.